Ante-Nicene authority and the Trinity in seventeenth-century England. Issue 1 (2nd January 2018) - Lucci, Diego
ABSTRACT: This article investigates the growth and decline of the use of the ante-Nicene Fathers in relation to Trinitarian issues in seventeenth-century Anglican apologetics. Anglican apologists referred to the writings of the ante-Nicene Fathers as the earliest and most reliable testimonies of Christianity contra what they perceived as Popish, Puritan, and Socinian corruptions of the true religion. On the other hand, Catholic, Reformed, and anti-Trinitarian polemicists stigmatized the incompatibility of the ante-Nicenes' writings with the Trinitarian dogma formulated at Nicaea and elaborated by the post-Nicene Fathers. In response, several Church of England divines attempted to defend their engagement with the ante-Nicene Fathers from the criticisms of Catholic, Reformed, and anti-Trinitarian polemicists, which exposed their use of the ante-Nicenes in Trinitarian matters to the charge of priestcraft. The historical narratives employed by Anglican apologists ultimately proved ineffective, and even provided various heterodox thinkers, such as John Toland, with additional arguments against the Trinitarian dogma.